Expression of KI-67, Cornulin and ISG15 in noninvolved mucosal surgical margins as predictive markers for relapse in oral squamous cell carcinoma (OSCC) / Lew Huai Lin - Lew, Huai Lin (2019)
Introduction: Relapse in OSCC is often observed in histologically non-involved surgical margins. This indicates possible presence of field alteration in the non-involved surgical margins, which in turn leads to local recurrence or second primary tumour. The identification of specific biomarkers that could predict relapse of OSCC would help the clinicians in treatment planning for patients. Objectives: The objectives of this study were to evaluate the expression of Ki-67, Cornulin and ISG15 in the non-involved surgical margins and its association with clinicopathological prognosticators and relapse of OSCC. Methods: Immunohistochemistry was used in staining of non-involved mucosal surgical margins from study (relapse) group (n = 23), control (non-relapse) group (n = 32) and normal oral mucosa (n = 5) with Ki-67, Cornulin and ISG15. Association between expression of markers with clinicopathological prognosticators and relapse in OSCC was analysed statistically using Chi-square tests. Binary logistic regression analysis was used to determine predictors of relapse in OSCC. Results: In the study group, significant low expression of Cornulin (p = 0.032) and ISG15 (p = 0.047) was observed. Low expression of Cornulin was also significantly associated with relapse (p = 0.004) of OSCC and primary tumours involving non-tongue sites (p = 0.013). Surgical margins exhibiting high expression of Ki-67 was significantly reduced in female patients (p = 0.041). Clinicopathological prognosticators such as age above 57.5 years (p < 0.001), Chinese ethnicity (p = 0.009), Indian ethnicity (p = 0.007), alcohol use (p = 0.025), epithelial dysplasia in surgical margins (p = 0.045) and type III and IV pattern of invasion of tumour (p = 0.007) were significantly associated with relapse of OSCC. Binary logistic regression analysis showed decreased expression of Cornulin (p = 0.018) and increased patient’s age (p = 0.008) were predictors of relapse in OSCC, with 34-fold risk and 18- iv fold risk, respectively. Conclusions: Relapse of OSCC could be predicted by decreased expression of Cornulin in the non-involved surgical margins. Validation of role of Ki-67 and ISG15 in predicting relapse of OSCC would require larger cohorts. Taken together, Cornulin as a predictor in relapse of OSCC was suggested. Keywords: OSCC, Relapse, Ki-67, Cornulin, ISG15